2017
DOI: 10.1142/s0217984917500257
|View full text |Cite
|
Sign up to set email alerts
|

Study of α-Fe2O3 formation and its measurement in oxide films of wheel surface during ELID grinding process

Abstract: This paper presents the study of forming mechanism of [Formula: see text]-Fe2O3 in oxide films on electrolytic in-process dressing (ELID) grinding wheel surface. To investigate the component content and the microtopography of oxide films, XRD, XPS, IR spectrum analysis, SEM, and TEM measurements are performed on ELID grinding wheels. In XRD test results, the characteristic absorption band of [Formula: see text]-Fe2O3 is found in the oxide film. XPS tests show that there is full of ferrous iron and oxygen eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Large quantities of α-Fe 2 O 3 particles are favorable, serving as an excellent agent for polishing in place of abrasive particles. Due to the absence of abrasive particles, our new diamond wheels address the issue of passivating particles that may detach and scratch the processed surface [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Large quantities of α-Fe 2 O 3 particles are favorable, serving as an excellent agent for polishing in place of abrasive particles. Due to the absence of abrasive particles, our new diamond wheels address the issue of passivating particles that may detach and scratch the processed surface [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…He studied the mechanical properties of oxide films on copper-based grinding wheels using the nanoindentation technology. Through experiments, he found that the hardness and elastic modulus of the oxide film are higher than those of the copper-based grinding wheel (Kuai et al, 2017a(Kuai et al, , 2017b(Kuai et al, , 2017c. He also studied forming mechanism of a-Fe 2 O 3 in oxide film on ELID grinding wheel surface and found that the oxide film can improve the grinding effect and the processing quality (Kuai et al, 2017a(Kuai et al, , 2017b(Kuai et al, , 2017c.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the surface precision of ultra-precision ELID grinding has reached nanometer level [3,4]. Therefore, any minor scratch will form defects on the machined ultra-precision surface, which will affect the surface quality [5]. There is a need to regrinding with no abrasive particles in the ultra-precision grinding stage.…”
Section: Introductionmentioning
confidence: 99%